Better boards towards higher profitability - Htay, Sheila Nu Nu (2011)
This paper will examine the impact of corporate governance on the profitability of banks using the agency theory. The profitability of banks is measured by return on assets (ROA) and return on equity (ROE). A total of twelve listed bank holding companies are examined over a ten-year period. Based on the panel data analysis, none of the conventional measures of corporate governance is significant as hypothesized. Board’s independence and institutional ownership have negative impact on ROE significantly. Apart from that, as the findings of the effect of corporate governance on bank profitability are inconclusive, other factors such as culture, local prevailing laws and business environment, might need to be considered.